2021
DOI: 10.3389/fncel.2020.613246
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Respond Rapidly to Ototoxic Injury of Lateral Line Hair Cells but Are Not Required for Hair Cell Regeneration

Abstract: The sensory organs of the inner ear contain resident populations of macrophages, which are recruited to sites of cellular injury. Such macrophages are known to phagocytose the debris of dying cells but the full role of macrophages in otic pathology is not understood. Lateral line neuromasts of zebrafish contain hair cells that are nearly identical to those in the inner ear, and the optical clarity of larval zebrafish permits direct imaging of cellular interactions. In this study, we used larval zebrafish to ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…We found that macrophages migrate into neuromasts within ∼2 hours of mechanical injury, where they contact hair cells and, in some cases, engulf hair-cell debris. Although this macrophage response is similar to that which occurs after ototoxic injury to neuromasts (Carrillo et al, 2016; Hirose et al, 2017; Warchol et al, 2021), the extent of hair cell loss after mechanical overstimulation is much less than the injury that occurs after ototoxicity. We observed macrophage entry in 30-40% of exposed neuromasts, despite modest hair cell loss (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…We found that macrophages migrate into neuromasts within ∼2 hours of mechanical injury, where they contact hair cells and, in some cases, engulf hair-cell debris. Although this macrophage response is similar to that which occurs after ototoxic injury to neuromasts (Carrillo et al, 2016; Hirose et al, 2017; Warchol et al, 2021), the extent of hair cell loss after mechanical overstimulation is much less than the injury that occurs after ototoxicity. We observed macrophage entry in 30-40% of exposed neuromasts, despite modest hair cell loss (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…We found that macrophages migrate into neuromasts within ~2 hr of mechanical injury, where they contact hair cells and, in some cases, engulf hair-cell debris. Although this macrophage response is similar to that which occurs after ototoxic injury to neuromasts ( Carrillo et al, 2016 ; Hirose et al, 2017 ; Warchol et al, 2020 ), the extent of hair-cell loss after mechanical overstimulation is much less than the injury that occurs after ototoxicity. We observed macrophage entry in 30–40% of exposed neuromasts, despite modest hair-cell loss ( Figure 6B and D ).…”
Section: Discussionmentioning
confidence: 55%
“…The inner ears of birds and mammals possess resident populations of macrophages, and additional macrophages are recruited after acoustic trauma or ototoxic injury ( Warchol, 2019 ). A similar macrophage response occurs at lateral line neuromasts of larval zebrafish after neomycin ototoxicity ( Warchol et al, 2020 ). Analysis of fixed specimens, as well as time-lapse imaging of living fish (e.g.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Treatment with neomycin for 30 min rapidly kills HCs by caspase-independent cell death (movieS2) ( 26 ). Macrophages start phagocytosing dead HCs as early as 15 min after the first cells die (movieS2-S3) ( 27 ). To describe the dynamics of effector macrophages from the time they enter the neuromast to when they leave during HC regeneration, we performed a macrophage recruitment assay.…”
Section: Resultsmentioning
confidence: 99%